The Connexion between Old and New - Bernard M. S. van Praag (Institute for the Study of Labor (IZA), 2004)
In this paper we compare the new satisfaction evaluation approach, developed in the nineties by Oswald, Clark, Blanchflower and others with the older income evaluation (IEQ) approach, developed by Van Praag and Kapteyn in the seventies of the previous century. We find that both approaches yield strikingly similar results with respect to financial satisfaction. The IEQ- approach yields additional insights, but it is not well applicable to other life domains than finance. It is argued that the usual Probit specification implies a specific cardinalization and, consequently, is less ordinal than usually thought. It is shown that the Probit-approach may be replaced by three other equivalent specifications that have some computational and intuitive advantages.
Keywords: I31; H31; C25; D31; C24; I39; 330; financial satisfaction; income evaluation; Probit-models; cardinal utility; Eigeninteresse; Nutzentheorie; Haushaltseinkommen